Dinamika Perubahan Sosial Upacara Adat Kebo-Keboan pada Masyarakat Using Desa Alasmalang Kecamatan Singojuruh Kabupaten Banyuwangi - Lestari, Dinna Eka Graha (Badan Riset dan Inovasi Daerah Provinsi Jawa Timur, 2020)
As the time and the modernization effect go on, the cultural value of a society experiences change toward modern society cultural value. Using Society can now be classified as modern society since they reflect the characteristics of modern society culture. The Kebo-keboan traditional ceremony can give a huge amount of income for the village. The income comes from the parking ticket, sponsors and regional government as well. Based on the situation and condition in field, the focuses of the research are: (1) The concept of the Kebo-keboan traditional ceremony in the Using society, (2) The change of Kebo-keboan traditional ceremony of the Using society, (3) The factors which causing the change of Kebo-keboan traditional ceremony of the Using society. Related to the focuses above, the approach used in the research is qualitative descriptive with the case study method, and using the data validity technique laid on trust, transformational, dependency and certainty based on objectivity.